Foreign Trade in the Austrian Regions - Roman Römisch (FIW - Research Centre International Economics, 2012)
This policy brief introduces a method to estimate foreign trade of the nine Austrian NUTS-2 regions. The basic idea of the method is to disaggregate national foreign trade data to the regional level using national input-output, regional employment and other supplemental data. This allows for the estimation of foreign trade of the Austrian regions for the years 1999 to 2009. The results indicate highly differentiated patterns of trade competitiveness across the Austrian regions. While Upper Austria and Vorarlberg perform well on European and global markets, other regions, foremost Burgenland, are in a much more difficult position. The regions' reactions to the 2009 economic crisis were equally differentiated. Although the decline of foreign trade led to an employment loss in all Austrian regions, Vorarlberg and Tyrol proved to be much more resilient than others.
Keywords: C82; F10; F14; F16; R1; R12; R15; 330; Austria; regions; Bundesländer; foreign trade; economic crisis